Systematic Review: Comparison of Telemedicine Consultation With Face-To-Face Consultation in High-Risk Pregnant Women in the Digital Era - Wahyuni Idvia Nova; Rezky Nindra R.A; Titin Marlina; Elfrida Y.A; Mufdlilhah Mufdlilhah; Putri Listiani6 (Universitas Malahayati Lampung, 2025)
ABSTRACT In the digital age, telemedicine has emerged as a promising approach to healthcare delivery, particularly for high-risk pregnant women who require regular monitoring and consultation. The shift from traditional face-to-face consultations to telemedicine consultations requires evaluation of its effectiveness and impact on maternal health.The aim of this systematic review was to compare the effectiveness and impact of telemedicine consultation with face-to-face consultation on the health of high-risk pregnant women. This comparison includes aspects such as patient satisfaction, quality of service, health outcomes, and implementation barriers. A systematic review was conducted using databases including PubMed, Sage Journal, Science Direct, Wiley, and Cochrane. The search was limited to articles published in the last five years (2019-2024). Additional references were identified through manual searches. Studies were selected based on predefined inclusion criteria with a focus on high-risk pregnant women and comparison of telemedicine and face-to-face consultations. The review included studies that provided data on patient satisfaction, quality of care, health outcomes, and implementation barriers. Telemedical consultations are generally well received by patients as they offer convenience and flexibility. However, challenges such as technological barriers, internet connectivity issues, and the need for emotional support were also noted. In terms of health outcomes, telemedicine proved to be as effective as face-to-face consultations for most measures, although some aspects of the service, particularly those that require direct physical assessment, are still a challenge. Telemedical consultations offer a viable alternative to face-to-face consultations for high-risk pregnant women, providing comparable quality of care and patient satisfaction. However, successful implementation of telemedicine requires addressing technological and emotional support challenges. Further studies with larger sample sizes and longer follow-up periods are needed to understand the long-term impact of telemedicine on maternal health. Keywords: Telemedicine, Face-to-face consultation, High-Risk Pregnant Women, Digital era